Spoilage bacteria of Penaeus indicus - Chandramohan, D., Chandrasekaran, M., Lakshmanaperumalsamy, P. and (Fishery Technology, 2021)
Bacteria isolated from raw (untreated and unprocessed) prawn (Penaeus indicus) stored at 28±2°C, 4°C and-18°C were tested for spoilage potential, namely, production of protease, lipase, amylase, reduction of trimethylamineoxide (TMAO) to trimethylamine (TMA), production of off odours from flesh broth and halo zone around the colony grown on flesh agar. About 63 % of the total isolates tested were potential spoilers. Members of Vibrio, Pseudomonas and Acinetobacter were found to be dominant potential spoilers at all temperatures.